Kemampuan Tanaman Mensiang (Scirpus grossus) dalam Menurunkan Kadar BOD dan COD Limbah Rumah Makan - Yasril Yasril; Awalia Gusti (Sanitasi: Jurnal Kesehatan Lingkungan, 2009)
Liquid waste yielded from food materials of restaurant is counted as organic waste which can be degradated by microorganisms becoming volatile and unpleasant odored compound. Therefore, further processing to decrease the BOD and COD concentration is needed, for example the application of Mensiang (Scirpus grossus) plants. The experiment study was a quasi one. The collected data was a primer ones which was gained from laboratory examination on the sample of the liquid wastes before and after been treated by the plants in detention time of 1, 2, and 3 days. The data was analyzed by using Anova statistical test to understand the differences amongst the variation of200, 400, and 600 gr weight of Scirpus grossus treatment, and amongst the variation of the detention times. The results showed that the average of the lowest BOD and COD concentration were in the 600 gr plants and one day detention time (i.e. 0,61 mg/l or 99,54 % reduction; and 24,75 mg/l or 92,35 % reduction). Meanwhile, the pH before and after the treatment were 5 and 8 respectively. It can be concluded that Scirpus grossus can be used to reduce BOD and COD concentration in restaurant liquid waste. Further study might be conducted for other types of the liquid waste.